2020
DOI: 10.1051/metal/2020040
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of non-metallic inclusions during heat treatment

Abstract: Isothermal heat treatment can not only modify steel microstructure, but also non-metallic inclusions. In this work, heat treatment experiments were conducted between 1373 and 1573 K (1100 and 1300 °C) to study the evolution of inclusion composition, morphology, and size distribution. Results showed that during the heat treatment at 1473 and 1573 K (1200 and 1300 °C), two main kinds of inclusions initially in the steel, CaS and MgO–Al2O3–CaO–CaS, gradually transformed to (Ca, Mn)S and MgO–Al2O3–(Ca, Mn)S inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…Integrated with the apparent area, the average chemical composition of the inclusions with different sizes could be calculated by Equation (5). [ 28 ] javg=k=1njk×Areakk=1nAreakwhere n represents the inclusion number in a specified size range; Areak and jk are the exposed apparent area and the chemical composition of a single inclusion ( k ), respectively; and javg represents the average chemical composition of the inclusions in the specified size range. As shown in Figure 3, the apparent radii of the inclusions mainly ranged from 0 to 5 μm.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Integrated with the apparent area, the average chemical composition of the inclusions with different sizes could be calculated by Equation (5). [ 28 ] javg=k=1njk×Areakk=1nAreakwhere n represents the inclusion number in a specified size range; Areak and jk are the exposed apparent area and the chemical composition of a single inclusion ( k ), respectively; and javg represents the average chemical composition of the inclusions in the specified size range. As shown in Figure 3, the apparent radii of the inclusions mainly ranged from 0 to 5 μm.…”
Section: Resultsmentioning
confidence: 99%
“…Integrated with the apparent area, the average chemical composition of the inclusions with different sizes could be calculated by Equation ( 5). [28] j avg ¼…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend is quite similar to that in the present study. In contrast, Liu et al [ 35 ] found that the inclusions of MgO–Al 2 O 3 –CaO–CaS system would change into MgO–Al 2 O 3 –(Ca, Mn)S inclusions during heat treatment. The CaO in the inclusions would react with the S and Al in steel to generate CaS and Al 2 O 3 .…”
Section: Discussionmentioning
confidence: 96%
“…Similar experiments were also carried out by Ren et al, [ 32–34 ] and they proposed that the evolution of MnO–SiO 2 system inclusions was closely related to heating temperature, inclusion size, and holding time as well as the contents of Cr and Si in steel. Liu et al [ 35 ] observed the inclusions in calcium‐treated Al‐killed steel after heat treatment and found that the inclusions of CaS and MgO–Al 2 O 3 –CaO–CaS in steel would transform into (Ca, Mn)S and MgO–Al 2 O 3 –(Ca, Mn)S inclusions, respectively. In addition, the average size of inclusions increased as well.…”
Section: Introductionmentioning
confidence: 99%